2019
DOI: 10.1007/s00394-019-02136-9
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary intake of total polyphenols and the risk of all-cause and specific-cause mortality in Japanese adults: the Takayama study

Abstract: Purpose Several epidemiological studies have demonstrated the health benefits of polyphenols, but the associations between polyphenol intake and mortality including total and major causes of death remain unclear. We investigated the associations between subjects' total polyphenol intake and their mortality from all causes, cardiovascular disease (CVD), cancer, and other causes of death in a population-based cohort study in Japan. Methods A total of 29,079 residents of Takayama City, Japan were analyzed. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
(63 reference statements)
0
18
0
1
Order By: Relevance
“…Bioactive compounds in these foods, however, have been shown to have anti-carcinogenic effects in experimental models and epidemiological studies [ 7 ]. For instance, high intake of fiber and polyphenols from cereals have been shown to reduce cancer mortality risk [ 65 , 66 , 67 ]. As for cancer incidence, a two-tier mechanism could explain how these compounds could prevent cancer mortality risk: first, fiber, mostly soluble fiber, modulates the gut microbiota composition improving the colonic barrier functions, and second, substrates such as resistant starch, non-starch polysaccharides (β-glucans), and phenols are metabolized into active metabolites by the commensal microbiota [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive compounds in these foods, however, have been shown to have anti-carcinogenic effects in experimental models and epidemiological studies [ 7 ]. For instance, high intake of fiber and polyphenols from cereals have been shown to reduce cancer mortality risk [ 65 , 66 , 67 ]. As for cancer incidence, a two-tier mechanism could explain how these compounds could prevent cancer mortality risk: first, fiber, mostly soluble fiber, modulates the gut microbiota composition improving the colonic barrier functions, and second, substrates such as resistant starch, non-starch polysaccharides (β-glucans), and phenols are metabolized into active metabolites by the commensal microbiota [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism underlying the combined effect remains unclear, the different antioxidants in CF and GT may additively strengthen the beneficial effects on body composition and cardiovascular parameters. In another population-based prospective study in Japan, the researchers found that dietary polyphenol intake is inversely associated with CVD [ 33 ]. To corroborate the association between polyphenols and CVD risk, more comprehensive studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intake of polyphenols is associated with a decreased risk of T2DM, metabolic syndrome, risk of ischemic stroke, non-fatal cardiovascular events risk, and risk of atherosclerotic vascular disease [ 254 ]. The Takayama study, consisting of over 29,000 Japanese individuals, found significantly lower CVD mortality in subjects with the highest polyphenol intake, as compared to those in the lowest quartile [ 255 ]. Inverse associations also existed for mortality from digestive diseases.…”
Section: Tanninsmentioning
confidence: 99%
“…Inverse associations also existed for mortality from digestive diseases. Polyphenols in this population were mainly derived from beverages such as green tea and coffee [ 255 , 256 ]. Consumption of proanthocyanidin-rich foods has been shown to reduce the risk of chronic kidney insufficiency and renal disease [ 257 ].…”
Section: Tanninsmentioning
confidence: 99%